Displacement, Borders, and Unsettling Narratives - Spiegel, Samuel J. author. aut Link
XXI, 144 p. 6 illus.
Keywords: This short book discusses some of the urgent critical debates regarding intercultural education on displacement during turbulent times of contentious border politics and ramped-up anti-migrant discourse. Drawing on original research and teaching insights from a team of co-authors from Pakistan, Iraq, Zimbabwe, Italy, India, Canada, the UK and beyond who are involved in teaching students from more than two dozen countries, it focuses on experiences of teaching in the midst of controversial refugee detention and deportation schemes – just some of many developments in the United Kingdom condemned strongly by several United Nations agencies. The authors’ analysis engages reflections, from diverse backgrounds and positionalities, on approaches to education that seek to deepen understandings of displacement experiences in an interconnected world as well as geopolitical responses, methodologies and representational practices. Dr. Samuel J. Spiegel has been teaching at the University of Edinburgh since 2011 and has published extensively on issues of mobility justice, migration, and political, ecological, cultural and socio-economic dimensions of displacement. A Senior Lecturer in International Development based at the Centre of African Studies, Dr. Spiegel currently serves as the Deputy Director of Research at the School of Social and Political Science. Blessing Mucherera, Sidra Idrees Francesco Moze Kanak Rajadhyaksha Boel McAteer1 Thabani Mutambasere1 Georgia Cole1 Jean-Benoit Falisse Savan Qadir.